PENERAPAN METODE INQUIRY TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU DALAM MATERI KERAGAMAN FLORA DAN FAUNA DI INDONESIA DI KELAS VII SMP NEGERI 1 TEBAS - Agus Suwarno (Universitas Muria Kudus, 2017)
The problem in this research is "Implementation Methods of Inquiry Against Student Results At Subjects IPS Integrated In Creative Diversity Flora And Fauna In Indonesia In Class VII Junior High School 1 Tebas", with sub-problems of research: (1) student learning control class who did not apply his method of inquiry in social studies Integrated in the material diversity of flora and fauna in Indonesia in class VII SMP Negeri 1 Tebas. (2) The results of the experimental class students learn to apply methods of inquiry in social studies Integrated in the material diversity of flora and fauna in Indonesia in class VII SMP Negeri 1 Tebas. (3) The difference in student learning outcomes with the experimental class control class that implements the method of inquiry in social studies Integrated in the material diversity of flora and fauna in Indonesia in class VII SMP Negeri 1 Tebas. The variables in this study consisted of the dependent variable and independent variables, the independent variable of this research is the result of learning and the independent variables are methods of inquiry. This study used an experimental method, the research is a form of quasi-experimental research or experiment with the study design quasy two-group post-test only design. The population in this study the entire seventh grade students totaling 196 people. The sampling technique using cluster sampling. Data collection techniques used in this study is the direct observation techniques, measurement techniques, and documentary techniques. And tools used are observation sheets (IPKG 2), achievement test, and documentation. Based on the analysis and discussion of data obtained: (1) the average student learning outcomes in control class is 69.62 which is quite enough. (2) The results of the calculation, the average student learning outcomes in the experimental class at 73.23 which is quite good. (3) based on calculations using the t test was obtained tcount ≥ ttable, 2.27 ≥ 2.00 then there is a difference in student learning outcomes with the experimental class control class that implements methods of inquiry.